INFLUENCE OF MICROALGAE ON THE GROWTH OF THE FRESH WATER ROTIFER Brachionus calyciflorus (PALLAS, 1766), LORETO, PERU - ISMIÑO-ORBE, Rosa Angélica (2022)
The objective of the present study was to evaluate the influence of chlorophytes on the population growth of the rotifer Brachionus calyciflorus. The experimental culture was carried out in nine 4 L polyethylene containers with a useful volume of 800 mL of filtered water where ten Brachionus calyciflorus rotifers were planted per container and fed with microalgae at a concentration of 6 x 106 cel mL-1: Chlorella sp. (Ch), Scenedesmus sp. (Sc) and Chlorella sp. + Scenedesmus sp. (Ch + Sc), during 15 days of culture. Rotifers were counted daily and population growth parameters were evaluated. The mean values of: temperature were 27,7 ± 0,31 o C, dissolved oxygen 4,9 ± 0,05 mg L-1 and pH 6,6 ± 0,22. The highest population values were with the mixture of Chlorella sp + Scenedesmus sp (yield of 1250 ± 523 ind mL-1, growth rate of 1.0 ±, 0,1 day, doubling time of 0,7 ± 0,1 day and the maximum density of organisms of 8142,9 ind mL-1). The feeding of the rotifers in the present study shows better population growth parameters with the mixture of Chlorella sp. and Scenedesmus sp.